1996
DOI: 10.1007/bf02213118
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography and granulocyte scintigraphy in active inflammatory bowel disease

Abstract: The accuracy of computed tomography (CT) and [99mTc]HMPAO granulocyte scintigraphy (GS) for detection of bowel localization, inflammatory activity, and complications in acute inflammatory bowel disease (IBD) was prospectively studied in 32 patients. Of each bowel segment, findings on CT and GS were scored by one blinded observer. Findings on operation or endoscopy served as the gold standard. In Crohn's disease (CD, 17 patients), CT detected bowel pathology (sensitivity 71%, specificity 98%), abscesses (sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…There is only one prospective study, in 13 patients with IBD, that compares CT with colonoscopy (63% of segments reached by colonoscopy, for a total of 44 bowel segments). 23 CT had a lower sensitivity than the 99m Tc-WBC scan for detecting bowel inflammation (68% for CT and 85% for 99m Tc-WBC). No controls or IBD patients with quiescent disease were included in this study to evaluate the specificity of the findings on CT or 99m Tc-WBC scans.…”
Section: Discussionmentioning
confidence: 83%
“…There is only one prospective study, in 13 patients with IBD, that compares CT with colonoscopy (63% of segments reached by colonoscopy, for a total of 44 bowel segments). 23 CT had a lower sensitivity than the 99m Tc-WBC scan for detecting bowel inflammation (68% for CT and 85% for 99m Tc-WBC). No controls or IBD patients with quiescent disease were included in this study to evaluate the specificity of the findings on CT or 99m Tc-WBC scans.…”
Section: Discussionmentioning
confidence: 83%
“…In children with true-negative results of 99m Tc-WBC imaging, there were 24 true-negative results of UGI-small bowel follow-through and four equivocal results (lymphoid nodular hyperplasia vs Crohn's disease). In adults, studies have also suggested that 99m Tc-WBC imaging is superior to contrast radiology in assessing the extent and activity of IBD [20,40].…”
Section: Technetium-99m Wbc Scintigraphy Versus Upper Gastrointestinamentioning
confidence: 96%
“…Scintigraphy with 99m Tc-labelled white blood cells (WBCs) is routinely used for the assessment of IBD [3], but the procedure is time consuming and scintigraphy using a new agent could replace this technique. 99m TcLeucoscan scintigraphy, which takes about 5 min and in addition does not require direct interaction with patients' blood, was thought to be an ideal candidate for this purpose.…”
Section: Dear Sirmentioning
confidence: 99%